EVALUATION OF GROUP COUNSELING PROGRAM ON SMP LABORATORIUM UNIVERSITAS NEGERI MALANG: DISCREPANCY MODEL - Saputra, Wahyu Nanda Eka (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2016)
Abstract. This study aims to determine the discrepancy between the performance of group counseling program on SMP Laboratorium Universitas Negeri Malang with standards. This study uses a standard of Guidelines for Performance Based Professional School Counselor Evaluation. Standard reads, “the professional school counselor counsels individual students and small groups of students with identified needs/concerns”. This study is an evaluation research using a discrepancy model. The approach used is a systems approach that is focused on the planning, implementation, and evaluation of group counseling programs. Based on the data analysis of evaluation of group counseling program in SMP Laboratorium Universitas Negeri Malang is still far from standard. Keyword: program evaluation, group counseling, discrepancy model